Influence of Surface Heterogeneity on Morphology of Interfacial Nanobubble - Yang, Haichang; Zhang, Fanfan; Xing, Yaowen; Gui, Xiahui; Cao, Yijun (Frontiers in Materials, 2022)
Gaseous domains formed on solid-liquid interface have attracted scientists’ attentions in recent two decades, and the existence of interfacial nanobubble (INB) has been basically confirmed. However, an overall understanding on INB is still lacking. This research studied the influence of surface chemical heterogeneity on the morphology of INB by molecular dynamics (MD) simulations technique. The results showed that the gaseous domains could not nucleate on the hydrophilic substrate, while only dense gas layer (DGL) could be observed from the time-averaged density map for homogeneously hydrophobic substrate due to the random moving of INB. If there was a hydrophobic patch on the hydrophilic surface, INB could form on the hydrophobic patch with contact line being pinned at the boundary of the patch. In this case, the contact angle (gas-side) increased with the gas oversaturation degree and decreased with surface hydrophobicity of the patch. For the case that there existed a more hydrophobic patch/site on the hydrophobic surface, the INB could have moved randomly along the hydrophobic surface, but its receding contact line was pinned by the more hydrophobic patch/site. Hence, the INB could only move in the vicinity of this pinning patch/site, so that an INB profile instead of a DGL formed due to the pinning effect, and the apparent contact angle of the INB is significantly lower than the actual one. Throughout this study, the apparent INB we observed from experiments may be different from its instantaneous state and is significantly affected by surface heterogeneity.